Surat dinas/resmi - Robby, Alief Maulana; Mustofa, Alvin Mohammad Nor; Novyanzi, Fawwaz Haka; Ramadhan, M. Rijal Ilham (Maliki Interdisciplinary Journal, 2025)
Official correspondence is an essential form of formal communication used to convey information, orders, reports, or notifications between organizations or relevant parties. This type of communication plays a crucial role in government, business, and other organizational settings. Writing official letters clearly and accurately greatly impacts the smoothness of communication and administrative processes. This paper discusses the definition of official letters, their purposes, various types, and the components that should be included in an official letter according to established guidelines. Additionally, this paper highlights the importance of legal and ethical considerations in writing official correspondence to ensure that the letter is properly understood and accepted by the recipient. It is expected that readers will gain a better understanding of how to draft effective official letters in accordance with correct procedures.